2009
DOI: 10.2174/1874946100902010023
|View full text |Cite
|
Sign up to set email alerts
|

The Prestige of Somatic and Mental Disorders: A Survey Among Health Professionals and a Representative General Population Sample

Abstract: Abstract:Objective: The purpose of the paper is to study the ranking of disorders according to their perceived importance. Previous studies suggest that rankings according to the perceived or attributed "value" or importance create informal hierarchies of disorders on normative attitudes about symptoms, treatment and outcome. In this work we studied disorder ranking in the general population and among health professionals, and some possible explaining factors. Data source: 1,127 adults representative of the No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…De oppsummerte erfaringene peker også på utfordringer med å kunne utvikle en volumkompetanse. Noen studier kan peke i retning av at helsepersonell både nedprioriterer og har negative holdninger til pasientgruppen (27)(28)(29), men konsekvensene for klinisk praksis er diskutable (30). Med forbehold om mulig selvseleksjon av leger med positive holdninger til pasientgruppen kan resultatene snarere gi et inntrykk av ønsker om å yte bedre proaktive og forebyggende tjenester, mer samarbeid med og konsultativ virksomhet fra spesialisthelsetjenesten, å kunne sette av ekstra tid til hver konsultasjon og å ivareta pasienten over lang tid.…”
Section: Fortolkningunclassified
“…De oppsummerte erfaringene peker også på utfordringer med å kunne utvikle en volumkompetanse. Noen studier kan peke i retning av at helsepersonell både nedprioriterer og har negative holdninger til pasientgruppen (27)(28)(29), men konsekvensene for klinisk praksis er diskutable (30). Med forbehold om mulig selvseleksjon av leger med positive holdninger til pasientgruppen kan resultatene snarere gi et inntrykk av ønsker om å yte bedre proaktive og forebyggende tjenester, mer samarbeid med og konsultativ virksomhet fra spesialisthelsetjenesten, å kunne sette av ekstra tid til hver konsultasjon og å ivareta pasienten over lang tid.…”
Section: Fortolkningunclassified
“…In general, categories of disease more common in young patients 14,15 ; those allowing for greater demonstration of "power" (e.g., specialist vs. general practitioner) 14 ; those whose treatments do not yield helplessness or dis gurement, 15 and; those that can be resolved or cured, 16 particularly via innovative or advanced technological or surgical interventions 14,17,18 are apportioned greater respect. Lower prestige is conferred on delocalized diseases -that is, those not con ned to a particular location in the body.…”
Section: Introductionmentioning
confidence: 99%
“…Lower prestige is conferred on delocalized diseases -that is, those not con ned to a particular location in the body. 14 In their study, exploring prestige rankings for somatic and mental disorders among health professionals and the general population, Pettersen et al 18 concluded that disorders attributed to imperfect lifestyle choices (rightfully or wrongfully) were allocated less prestige.…”
Section: Introductionmentioning
confidence: 99%